Preparation of Carbon Nitride Dots with Sizes Larger than 20 nm - Peihui Luo; Yunlong Yu; Xiangfeng Guan (Applied Sciences, 2019)
Carbon nitride dots (CNDs) were obtained via carbonization of polymer formed via the reaction of 1, 2-ethylenediamine (EDA) and CCl4. The average diameter of CNDs is calculated to be ca. 44 nm. They possess solubility in water and polar organic solvents.